2004
DOI: 10.1159/000079260
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Outcomes as a Function of Baseline Severity of Ischemic Stroke

Abstract: Background: The spectrum of neurological impairments following acute ischemic stroke is broad. The initial stroke severity predicts responses to treatment and outcomes after ischemic stroke. While clinical trials are using baseline severity as an enrollment criterion or a stratified variable, adjustment of outcome measures as a function of initial impairments has not been done. Methods: We developed a responder analysis that defines favorable outcomes at 90 days as influenced by the baseline National Institute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
84
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 10 publications
2
84
0
Order By: Relevance
“…Recently it was suggested that this method is useful for detecting a true signal and improving study power. 30,31 The simple dichotomization of function outcome (mRS scores 0-2 vs 3-5), which was performed as a sensitivity analysis in this study, provided similar results.…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…Recently it was suggested that this method is useful for detecting a true signal and improving study power. 30,31 The simple dichotomization of function outcome (mRS scores 0-2 vs 3-5), which was performed as a sensitivity analysis in this study, provided similar results.…”
mentioning
confidence: 58%
“…During the acute stage of ischemic stroke, high BP variability may be associated with lesion growth. 4,29 Autoregulation may also be impaired in the subacute stage, 30,31 and a hypoperfused brain is more likely to be affected by systemic BP changes. However, it should be noted that these explanations are speculative.…”
mentioning
confidence: 99%
“…NIHSS was divided into 4 categories of severity as previously published: 0 ϭ NIHSS 0 -7; 1 ϭ NIHSS 8 -14; 2 ϭ NIHSS 15-20; 3 ϭ NIHSS Ͼ20. 21 For occlusion location, proximal occlusions (ICAproximal M1) were scored 1 and distal occlusions (distal M1-M4) were scored 0. The CMR score was the sum of the stratified NIHSS score plus the occlusion score; the total CMR score for each patient ranged from 0 -4.…”
Section: Discussionmentioning
confidence: 99%
“…On both the 30 th and 90 th day, stroke outcomes were assessed using two different criteria. In the first outcome model, favorable outcomes [I] were simply defined by mRS scores (≦ 1), while the favorable outcomes [II], a method by Adams et al, were defined as follows: a) a 90-day mRS score of 0, if the baseline NIHSS scores were < 8, b) a mRS score of 0 or 1, if the NIHSS scores were 8-14, c) a mRS score 0-2, if the NIHSS scores were > 14 points [27].…”
mentioning
confidence: 99%